Old age promotes retinal fibrosis in choroidal neovascularization through circulating fibrocytes and profibrotic macrophages - Caijiao Yi; Jian Liu; Wen Deng; Chang Luo; Jinyan Qi; Mei Chen; Heping Xu (Journal of Neuroinflammation, 2023)
Abstract Background Retinal fibrosis affects 40–70% of neovascular age-related macular degeneration patients. This study investigated the effect of ageing on subretinal fibrosis secondary to choroidal neovascularization and the mechanism of action. Methods Subretinal fibrosis was induced in young (2.5-month) and aged (15–16-month) C57BL/6J mice using the two-stage laser protocol. Five and 30 days later, eyes were collected and stained for CD45 and collagen-1 and observed by confocal microscopy. Fibrocytes (CD45+collagen-1+) were detected in the bone marrow (BM), blood and fibrotic lesions by flow cytometry and confocal microscopy, respectively. BM-derived macrophages (BMDMs) were cultured from young and aged mice with or without TGF-β1 (10 ng/mL) treatment. The expression of mesenchymal marker αSMA (Acta2), fibronectin (Fn1) and collagen-1 (Col1a1) was examined by qPCR and immunocytochemistry, whereas cytokine/chemokine production was measured using the Luminex multiplex cytokine assay. BM were transplanted from 22-month (Ly5.2) aged mice into 2.5-month (Ly5.1) young mice and vice versa. Six weeks later, subretinal fibrosis was induced in recipient mice and eyes were collected for evaluation of fibrotic lesion size. Results Under normal conditions, the number of circulating fibrocytes (CD45+collagen-1+) and the expression levels of Tgfb1, Col1a1, Acta2 and Fn1 in BMDMs were significantly higher in aged mice compared to young mice. Induction of subretinal fibrosis significantly increased the number of circulating fibrocytes, enhanced the expression of Col1a1, Acta2 and Fn1 and the production of soluble urokinase plasminogen activator surface receptor (suPAR) but decreased the production of CXCL10 in BMDMs. BMDMs from aged subretinal fibrosis mice produced significantly higher levels of VEGF, angiopoietin-2 and osteopontin than cells from young subretinal fibrosis mice. The subretinal fibrotic lesion in 15–16-month aged mice was 62% larger than that in 2.5-month young mice. The lesion in aged mice contained a significantly higher number of fibrocytes compared to that in young mice. The number of circulating fibrocytes positively correlated with the size of subretinal fibrotic lesion. Transplantation of BM from aged mice significantly increased subretinal fibrosis in young mice. Conclusions A retina–BM–blood–retina pathway of fibrocyte/macrophage recruitment exists during retinal injury. Ageing promotes subretinal fibrosis through higher numbers of circulating fibrocytes and profibrotic potential of BM-derived macrophages.